Novel components for supporting adaptivity in education systems - model-based integration approach - CONLAN, OWEN (My University, 2000)
A Hypermedia System is collection of linked nodes (hyperdocuments), which have links through which the student can traverse to other nodes [Brusilovsky, 96], [De Bra, 98]. In Intelligent Tutoring Systems (ITS) the content or presentation is modified based on the interactions between the student and the system. ITSs incorporate artificial intelligence techniques so that the instruction is adaptable to the learners needs and styles [Boyd, 93]. Intelligence techniques such as curriculum sequencing, interactive problem solving support and intelligent analysis of student solutions characterise ITSs. The main criticism in the past has been that ITSs are based on the premise that for learning to occur, it is sufficient to embed an experts knowledge in the structure of the content and apply an appropriate instructional design model [Stauffer, 96].
PUBLISHED
Keywords: Computer Science